2002
DOI: 10.1136/bmj.324.7338.639
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of evidence based leaflets in maternity care

Abstract: Objective To examine the use of evidence based leaflets on informed choice in maternity services. Design Non-participant observation of 886 antenatal consultations. 383 in depth interviews with women using maternity services and health professionals providing antenatal care. Setting Women's homes; antenatal and ultrasound clinics in 13 maternity units in Wales. Participants Childbearing women and health professionals who provide antenatal care. Intervention Provision of 10 pairs of Informed Choice leaflets for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
160
3
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 19 publications
12
160
3
4
Order By: Relevance
“…A study of the effectiveness of 10 'informed choice' leaflets for pregnant women in Wales found that they did not promote informed choice. 8 For example, many were withheld from women, or lost amidst other written information, and there was little opportunity for discussion. The amount of positive information about Down's syndrome in the written information from the UK may reflect social attitudes towards this condition in the UK and/or the influence of The Down's Syndrome Association, a large national charity which champions the rights of people with Down's syndrome and strives to improve knowledge of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the effectiveness of 10 'informed choice' leaflets for pregnant women in Wales found that they did not promote informed choice. 8 For example, many were withheld from women, or lost amidst other written information, and there was little opportunity for discussion. The amount of positive information about Down's syndrome in the written information from the UK may reflect social attitudes towards this condition in the UK and/or the influence of The Down's Syndrome Association, a large national charity which champions the rights of people with Down's syndrome and strives to improve knowledge of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…"Socially complex interventions", such as the Informed Choice leaflets, should be valuated within the context in which they are used and through a prudent combination of qualitative and quantitative methods. [21] Therefore, assessment of quality of family planning service at any level in our country is very important. Increasing quality of family planning service could help to sustain contraceptive use.…”
Section: Introductionmentioning
confidence: 99%
“…This is surprising since less educated woman are more likely to have a Caesarean section (TollĂĽnes et al 2007). In a qualitative study, Stapleton et al (2002) showed that pregnant women normally follow the advice of their gynaecologist, who usually fails to adequately inform them about the risks of a technical intervention. In a retrospective study (Mould et al 1996), 51.7% (15 of 29) of women who had undergone an elective Caesarean section felt that they had made a significant or full contribution towards the decision, and 31.0% were of the opinion that they had made only a small contribution or none at all.…”
Section: Introductionmentioning
confidence: 99%